The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/jbm.a.35915
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive glass‐based surfaces induce differential gene expression profiling of osteoblasts

Abstract: The ability of Biosilicate® with two crystalline phases (BioS-2P) to drive osteoblast differentiation encourages the investigation of the cellular mechanisms involved in this process. Then, the aim of our study was to analyze the large-scale gene expression of osteoblasts grown on BioS-2P compared with Bioglass 45S5 (45S5). Osteoblasts differentiated from rat bone marrow mesenchymal stem cells were cultured under osteogenic conditions on BioS-2P, 45S5 and polystyrene (control). After 10 days, the expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The metabonegenic mechanism may be worthy of future study to explore whether nutrient-or energysensing pathways (e.g., the mTOR and the AMPK pathways) are involved in citrate metabonegenic regulation, especially since citrate uptake increased mTOR-dependent protein synthesis and diminished the hypothalamic AMPK activity following exogenous supplementation (40). Moreover, the involvement and upregulation of SLC13a5 rather than SLC16a1 as the lactate membrane transporter during active bone formation (10,11,41) highlights the advantages of citrate-based materials for orthopedic applications compared with traditional PLA-based materials.…”
Section: Discussionmentioning
confidence: 99%
“…The metabonegenic mechanism may be worthy of future study to explore whether nutrient-or energysensing pathways (e.g., the mTOR and the AMPK pathways) are involved in citrate metabonegenic regulation, especially since citrate uptake increased mTOR-dependent protein synthesis and diminished the hypothalamic AMPK activity following exogenous supplementation (40). Moreover, the involvement and upregulation of SLC13a5 rather than SLC16a1 as the lactate membrane transporter during active bone formation (10,11,41) highlights the advantages of citrate-based materials for orthopedic applications compared with traditional PLA-based materials.…”
Section: Discussionmentioning
confidence: 99%
“…43,44 The osteoblastic differentiation has been characterized by the gene expression of bone markers, alkaline phosphatase activity, and deposition of mineralized matrix. [43][44][45] Regarding the origin, the clustering of samples showed that MSCs from both sources present similar gene expression profiles, but differences in the expression of genes directly related to the processes of osteoblast differentiation and osteogenesis, such as Ibsp, Alpl, and Dlx5, suggest that BM-MSCs are more committed to osteoblast differentiation, which positively affects the osteogenic potential of these cells. For instance, the overexpression of Dlx5 inhibits adipocyte differentiation while inducing osteoblast differentiation of MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the growth of an apatite‐like layer may provide an ideal environment for osteoblast colonization, proliferation, and differentiation (Jell & Stevens, ; Zhao et al, ). Moreover, BG extracts deeply impact the gene expression of osteoblasts, and this effect may be, at least in part, associated with their osteostimulation ability (de Godoy et al, ; Ferraz et al, ; Xynos et al, ). The up‐regulation of genes previously recognized as participating in the mineralization process (e.g., Bglap, Dmp1, Rcor2, and Phospho1) indicates a more advanced stage of osteoblast differentiation when these cells are cultured in contact with BGs (Ferraz et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, chemical signals delivered from BGs, mainly ionic products, have been widely reported to promote matrix synthesis of fibroblasts and angiogenic differentiation of endothelial cells (Gorustovich, Roether, & Boccaccini, 2010;Shih, Lu, Hsieh, Chen, & Chen, 2014). The calcium phosphate layer spontaneously produced after BG contact with body fluids can form a chemical bond with bone and dissolve over time, provoking bone cell activity through the up-regulation of several genes in osteoblasts (Ferraz et al, 2017;Hoppe et al, 2011;Xynos, Edgar, Buttery, Hench, & Polak, 2001). All these characteristics have made them attractive to many applications in tissue engineering, particularly in orthopaedic and dentistry fields (Habraken, Habibovic, Epple, & Bohner, 2016).…”
Section: Introductionmentioning
confidence: 99%